A calibration strategy for vision-guided robot assembly system of large cabin. (15th October 2020) - Jiang, Tao; Cui, Haihua; Cheng, Xiaosheng
Highlights: Calibration procedures for vision-based robot assembly of large cabin is proposed. Optimized homography matrix are proposed for large FOV camera calibration. A special small base target (SBT) is designed and the calibration method is proposed. The calibration results are verified with simulation and real data. Abstract: Vision measurement technology is increasingly utilized in aerospace assembly due to its high precision, low cost and convenience. However, it remains challenges to calibrate the visual measuring equipment and the global assembly station due to complex shape, large volume and high precision requirement. This paper proposes a calibration strategy for large cabin assembly system (LCSS) with vision guidance, focusing on calibration of binocular vision, small base target (SBT) and global station. A combined large plane target (CLPT) calibration method with optimized homography matrix is proposed. Then a profiling copy SBT is developed and the special calibration method based on common point and common cylinder is proposed. The LCSS is globally calibrated at last. Numerical simulations are implemented to test the calculation method and the noise effect. Also, real data experiments of binocular vision calibration and global calibration of LCSS are developed to verify the proposed method.